1995
DOI: 10.1159/000282747
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Metachronous Testicular Germ Cell Tumors Occurring in Two Non-Twin Brothers

Abstract: We report here the familial occurrence of bilateral testicular germ cell tumors in 2 non-twin brothers, developing after an interval of 16 and 4 years, respectively. To our knowledge, this is the first report on the occurrence of metachronous and bilateral testicular tumors in non-twin brothers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1997
1997
2003
2003

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Thus, reports of more than two family members having GCT 7,10,24 as well as reports of the coincidence of famil-the results of the current study agree only in part with the results of the study by Nicholson and Harland. 6 A ial and bilateral GCT, 7,25 and associations of GCT with several urogenital developmental anomalies have conflicting result was reported in a recent study from Denmark, 11 in which no age difference was found be-been reported. 8,26,27 Epidemiologic evidence comes from racial differences in the incidence of GCT 28 and tween FTC cases and sporadic cases, not even in separate analysis of the different histologies.…”
Section: Proportions Of Familial Testicular Cancermentioning
confidence: 94%
“…Thus, reports of more than two family members having GCT 7,10,24 as well as reports of the coincidence of famil-the results of the current study agree only in part with the results of the study by Nicholson and Harland. 6 A ial and bilateral GCT, 7,25 and associations of GCT with several urogenital developmental anomalies have conflicting result was reported in a recent study from Denmark, 11 in which no age difference was found be-been reported. 8,26,27 Epidemiologic evidence comes from racial differences in the incidence of GCT 28 and tween FTC cases and sporadic cases, not even in separate analysis of the different histologies.…”
Section: Proportions Of Familial Testicular Cancermentioning
confidence: 94%
“…Some data suggest that the relative familial risk of TGCTs is higher for most other types of cancers (for review, see 46). There are numerous reports on families with at least two brothers affected by testicular cancer (7, 8, 47, 48), some reporting on bilateral cases (49). Accordingly, a study reported a higher incidence of bilateral cases vs unilateral in familial cases in comparison with sporadic (6); however, the TGCTs of the two brothers in the present study were both unilateral.…”
Section: Discussionmentioning
confidence: 99%